Belarus: Sovereignty under threat. Impacts of the Russian war against Ukraine - Manfred Huterer; Astrid Sahm (Stiftung Wissenschaft und Politik (SWP), 2024)
Russia's full-scale invasion of Ukraine in February 2022 also called the sovereignty of Belarus into question. The country served as a launching pad for the attack, thus becoming a co-aggressor. However, relations between Minsk and Moscow changed the longer the war has lasted. Belarusian leader Lukashenka has increasingly acted like a self-confident war service provider toward Kremlin boss Putin. At the same time, he has been able to avoid any direct military involvement and has sought to preserve his chance at serving as a mediator. Nevertheless, Belarus' structural dependence on Russia has continued to increase in many areas. Right now, this gradual loss of sovereignty can still be reversed. In order for this to remain the situation, the EU and Germany must not write the country off.
Keywords: 320; Belarus; Russia; Russia's war of aggression against Ukraine; Alexander Lukashenka; Vladimir Putin; Yevgeny Prigozhin; Union State of Russia and Belarus